Hubungan Kualitas Pelayanan kepada Pasien Terhadap Minat Kunjungan Ulang di Instalasi Rawat Jalan Rumah Sakit Umum Daerah Kecamatan Mandau Kabupaten Bengkalis Tahun 2017: Hubungan Kualitas Pelayanan kepada Pasien Terhadap Minat Kunjungan Ulang di Instalasi Rawat Jalan Rumah Sakit Umum Daerah Kecamatan Mandau Kabupaten Bengkalis Tahun 2017 - Andriane, Madya; Susmaneli, Herlina (Jurnal Kesehatan Komunitas, 2018)
Community users of health services increasingly demand quality services. The better quality of the services provided, the more will increase the patient's interest to re-visit. The number data of patient visits in the outpatient installation in 2017 tended to decrease compared to 2016. From the data of the decrease in the number of outpatient visits, obtained from 3 polyclinics have decrease of patient visit, that is: polyclinic of internal medicine, child polyclinic and obstetric polyclinic. Whereas RSUD Mandau Sub-District, continues to strive to provide a good service for the interest of patient visit increases. The purpose of this research is to know the relation of patient service quality and re-visit of outpatient installation at Regional Hospital, Mandau Sub-District, Bengkalis Regency, based on reliability, responsiveness, assurance, empathy and direct evidence. The study is quantitative observational analytic with cross-sectional design analytic study (cross-sectional). The number of samples in this study are patients from 3 polyclinics of Mandau District General Hospital of Bengkalis Regency (polyclinic of internal medicine, child polyclinic and obstetric polyclinic) conducted in December 2017. The sample was taken by using hypothesis test-two proportion formula with 82 patients. The result of multivariate analysis shown that the most influence variable of re-visit interest is emphaty (OR: 31,063) and reliability and responsiveness as confounding variable. Therefore required to improve quality of service, mostly on making patients feel safe and comfortable during medical treatment, by giving reward for employee who give best services